Vibration Reduction Performance of a Novel Harmonic Frequency Damping Device for Damping Pad Floating Slab Track - Zhaowei Chen; Hanbo Zhang; Qianhua Pu; Pengfei Xu; Zhihui Chen (Buildings)
The stability of the damping pad floating slab track (DPFST) plays a critical role in the operational safety and passenger comfort of urban rail transit systems and represents a significant technical challenge. This paper introduces a novel harmonic frequency damping device (HFDD) with preload characteristics to enhance DPFST stability. First, the rubber damping pad’s constitutive relationship is determined using uniaxial tensile tests and the Mooney–Rivlin model. Next, a vehicle–track coupled dynamic model and a finite element model of the DPFST with HFDD are developed. Finally, the effects of HFDD installation and parameter adjustments on the DPFS’s modal and dynamic responses are examined. Results show that the HFDD effectively adjusts the DPFS’s natural frequency and suppresses its acceleration and displacement. Increasing HFDD stiffness from 0 to 10 kN/mm raises the DPFS’s natural frequency by up to 7.58 Hz. Within the stiffness and damping ranges of 0–20 kN/mm and 0–100 kN·s/m, respectively, the HFDD significantly reduces DPFS vibration, with maximum reductions in acceleration of 45.64% and 64.24% and in displacement of 47.55% and 39.06%. However, beyond these ranges, further increases in stiffness and damping substantially reduce the HFDD’s vibration suppression effectiveness and excessively high values are impractical for engineering use.